Rituximab for recurrent IgA nephropathy in kidney transplantation: A report of three cases and proposed mechanisms. Issue 1 (January 2017) - Chancharoenthana, Wiwat; Townamchai, Natavudh; Leelahavanichkul, Asada; Wattanatorn, Salin; Kanjanabuch, Talerngsak; Avihingsanon, Yingyos; Praditpornsilpa, Kearkiat; Eiam‐Ong, Somchai
Abstract: Aim: Recurrent IgA nephropathy (IgAN) is a common recurrent glomerular disease after kidney transplantation. Recurrent IgAN, in particular, with crescent formation or endocapillary proliferation might result in kidney allograft loss. However, the current treatment options of recurrent IgAN are conflicting. Methods: We have reported three kidney‐transplanted recipients with biopsy‐proven recurrent IgAN treated with four consecutive months of rituximab at the dose of 375 mg/1.73m 2 without corticosteroids. Results: At median follow‐up 20 months following rituximab administration, all three recipients demonstrated decrease in proteinuria severity, slow disease progression with a well‐tolerated condition. This therapeutic effect is most probably mediated by the B cell depletion. Conclusion: Our three case reports suggest that the disease severity of recurrent IgAN with endocapillary proliferation regardless of crescent formation can be minimized by the four doses of monthly rituximab regimen. Summary at a Glance: This is a case series of three kidney transplant recipients showing the potential benefit of treatment with rituximab in recurrent IgA nephropathy.